Soft X‐ray Imaging of the Magnetosheath and Cusps Under Different Solar Wind Conditions: MHD Simulations. Issue 4 (1st April 2019) - Sun, T. R.; Wang, C.; Sembay, S. F.; Lopez, R. E.; Escoubet, C. P.; Branduardi‐Raymont, G.; Zheng, J. H.; Yu, X. Z.; Guo, X. C.; Dai, L.; Liu, Z. Q.; Wei, F.; et al.
Abstract: The soft X‐ray emissions from the Earth's magnetosheath and cusp regions are simulated under different solar wind conditions, based on the PPMLR‐MHD code. The X‐ray images observed by a hypothetical telescope are presented, and the basic responses of the magnetopause and cusp regions are discernable in these images. From certain viewing geometries, the magnetopause position in the equatorial plane, as well as the latitudinal scales and azimuthal extent of cusp can be directly extracted from the X‐ray images. With these reconstructed positions, the issues we are able to analyze include but are not limited to the compression of magnetopause and widening of the cusp after an enhancement of solar wind flux, as well as the erosion of the magnetopause and equatorward motion of cusp after the southward turning of the interplanetary magnetic field. Hence, the X‐ray imaging is an appropriate technique to study the large‐scale motion of magnetopause and cusps in response to solar wind variations. Key Points: X‐ray images are estimated based on MHD simulations under different solar wind conditions Responses of the magnetopause to solar wind changes are analyzed from X‐ray images Responses of the cusp to solar wind variations are presented via X‐ray images